Novel Brunei Darussalam: Satu Pembicaraan tentang Pengutaraan Pemikiran - Haji Morsidi (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2009)
This paper will discuss several Brunei novels which contain the spelling out of thoughts and culture. There are novels which spell out new thoughts, yet inside also contain elements of Brunei culture leading to the concept or philosophy of Melayu Islam Beraja (M.I.B), For example, some novels speak about the problem of development, which has to be in accordance with Islam, nation's identity, country and culture This can be seen in the novels Sumbangsih Seni (1997) written by Ampuan Brahim Ampuan Haji Tengah and Hadiah Sebuah Impian (1983) by Muslim Burmat. Some other novels mark the importance of defending the nation's dignity and identity, this can be seen in Pahlawan Pengiran Sakam (1993) written by Mohd. Salleh Abdul Latiff and Urth Pesisir (2005) by Muslim Burmat. Another novel, Menyerah (1985) by Leman Ahmad, mounts the spirit of loving the country and the responsibility owed to one's family, society, nation and country. Thus, it can be said that even though some Brunei novels produced by several authors contain new thoughts, they stil also consider defending the nation's identity, religion and culture as something important.